GAMBARAN TINGKAT KECEMASAN PADA PASIEN KANKER YANG MENJALANI KEMOTERAPI DI RSUD Dr. M. YUNUS BENGKULU - Listyana Hafsah (Universitas Bengkulu, 2022)
Chemotherapy can cause physiological and psychological impacts, one of the psychological effects that often arises is anxiety. This study aims to describe the level of anxiety in cancer patients undergoing chemotherapy. This type of research is quantitative descriptive. The sampling method is by accidental sampling. The sample of this study was cancer patients undergoing chemotherapy with a total of 36 samples. The instrument used is STAI (State-Trait Anxiety Inventory). The results of this study showed that a small portion (28%) of respondents experienced mild anxiety, more than some (53%) of respondents experienced moderate anxiety and a small proportion (19%) of respondents experienced severe anxiety. To reduce the anxiety level of cancer patients undergoing chemotherapy, it is hoped that nurses in the chemotherapy room can make palliative care effective, such as giving more attention and motivating families to provide more support for cancer patients undergoing chemotherapy.